L' orda d'oro 1968-1977 : la grande ondata rivoluzionaria e creativa, politica ed esistenziale - Balestrini, Nanni; Moroni, Primo; Bianchi, Sergio; Berardi, Franco; Chiaromonte, Franca; Daghini, Giairo; Paolozzi, Letizia (Milano : Feltrinelli, 1988)
Bibliotheek François Vercammen
Italiaans
Monografie
Keywords: arbeidersbeweging; jeugdbewegingen; protest; Italië